Analysis of Entrepreneurial Orientation on Business Performance through Competitive Advantage as a Mediating Variable - Yahmardiana, Aini; Danial, R. Deni Muhammad; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the mediating effect of competitive advantage in the relationship of entrepreneurial orientation to business performance. The research method used in this research is quantitative research method with associative descriptive approach. The sample technique used was saturated sample by distributing questionnaires to 100 skincare and cosmetic stores in Sukabumi and the data analysis technique was Structural Equation Modeling (SEM) with the help of PLS software. The results of this study indicate that Skincare and Cosmetic Stores in Sukabumi have succeeded in building entrepreneurial orientation, competitive advantage and good business performance in Skincare and Cosmetic Stores in Sukabumi. Entrepreneurial orientation has a direct and significant effect on competitive advantage, competitive advantage has a direct and significant effect on business performance and excellence mediates effectively in the leadership relationship of entrepreneurial orientation to business performance. The direct relationship effect of entrepreneurial orientation on business performance is smaller than the indirect effect. Thus, it can be concluded that competitive advantage acts as a mediating relationship between entrepreneurial orientation and business performance.